USE RUBRIC IN TEACHING GEORGIAN AS A FOREIGN LANGUAGE - Mikadze, Manana ("Intercultural Dialogues" Transactions, 2025)
The article is dedicated to the usage of self-assessment and peer-assessments. Creating rubrics and displaying them in classroom settings makes foreign language learning not only active but effective as well. That’s why designing language skills rubrics and introducing them to students maintains active learning as they (students) become mutual independent assessors of their knowledge and their mates’ abilities. As well rubrics give opportunities to parents to control and actively be involved in their children’s learning process.